267. 95cm^3
hope this helped
You take the first equation and make a value for y. So 6x + y =7 change it to :
y = -6x + 7
Now in the second equation replace the “y” with -6x +7 this is what it means to use substitution method . Your combined equation will now be :
8x + 9(-6x + 7) =17
Now do distributive property and you get :
8x + -54x +63 =17
Now combine like terms ;
-46x +63 =17
-46x =-46
x = 1
Now replace 1 for X value and we can get the value of Y .
Y=1
X=1
Answer:
C. x² + 7
Step-by-step explanation:
If f(x) = 2x² + 5 and g(x) = x² - 2, then
(f - g)(x) = f(x) - g(x)
= (2x² + 5) - (x² - 2)
= 2x² + 5 - x² + 2
= 2x² - x² + 5 + 2
= x² + 7
Answer:
(4, -2)
Step-by-step explanation:
To find the midpoint of two points you have to take the average of those two points. So, I can do (1+8)/2, which is 4, to find the midpoint of the x coordinates. I can then do (-9+5)/2, which is -2 to find the midpoint of the y coordinates.